Multiple expression cassette exchange via TP901‐1, R4, and Bxb1 integrase systems on a mouse artificial chromosome. Issue 3 (28th January 2017) - Tomimatsu, Kosuke; Kokura, Kenji; Nishida, Tadashi; Yoshimura, Yuki; Kazuki, Yasuhiro; Narita, Masashi; Oshimura, Mitsuo; Ohbayashi, Tetsuya
Abstract : The site‐specific excision of a target DNA sequence for genetic knockout or lineage tracing is a powerful tool for investigating biological systems. Currently, site‐specific recombinases (SSRs), such as Cre or Flp recombination target cassettes, have been successfully excised or inverted by a single SSR to regulate transgene expression. However, the use of a single SSR might restrict the complex control of gene expression. This study investigated the potential for expanding the multiple regulation of transgenes using three different integrase systems (TP901‐1, R4, and Bxb1). We designed three excision cassettes that expressed luciferase, where the luciferase expression could be exchanged to a fluorescent protein by site‐specific recombination. Individual cassettes that could be regulated independently by a different integrase were connected in tandem and inserted into a mouse artificial chromosome (MAC) vector in Chinese hamster ovary cells. The transient expression of an integrase caused the targeted luciferase activity to be lost and fluorescence was activated. Additionally, the integrase system enabled the specific excision of targeted DNA sequences without cross‐reaction with the other recombination targets. These results suggest that the combined use of these integrase systems in a defined locus on a MAC vector permits the multiple regulation of transgene expression and might contribute to genomic or cell engineering. Abstract : We generated a reporter system to evaluate the precise target DNA excision for three distinct integrases, TP901‐1, R4, and Bxb1. Using this reporter system, we marked cells with up to eight different expression patterns of fluorescent proteins after the transient expression of specific integrases. The reporter system was inserted into a mouse artificial chromosome vector for the stable expression of reporters.